Thermal Stability of Globins: Implications of Flexibility and Heme Coordination Studied by Molecular Dynamics Simulations - Julió Plana, Laia (2019)
Proteins are sensitive to temperature, and abrupt changes in the normal temperature conditions can have a profound impact on both structure and function, leading to protein unfolding. However, the adaptation of certain organisms to extreme conditions raises questions about the structural features that permit the structure and function of proteins to be preserved under these adverse conditions. To gain insight into the molecular basis of protein thermostability in the globin family, we have examined three representative examples: human neuroglobin, horse heart myoglobin, and Drosophila hemoglobin, which differ in their melting temperatures and coordination states of the heme iron in the absence of external ligands. In order to elucidate the possible mechanisms that govern the thermostability of these proteins, microsecond-scale classical molecular dynamics simulations were performed at different temperatures. Structural fluctuations and essential dynamics were analyzed, indicating that the flexibility of the CD region, which includes the two short C and D helixes and the connecting CD loop, is directly related to the thermostability. We observed that a larger inherent flexibility of the protein produces higher thermostability, probably concentrating the thermal fluctuations observed at high temperature in flexible regions, preventing unfolding. Globally, the results of this work improve our understanding of thermostability in the globin family.